La manticora e la sfinge. Echi d’Oriente nei depositi della Ca’ d’Oro - Riccioni, Stefano (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
The article examines two marble fragments dated, on stylistic grounds, around the middle of the 12th century, and preserved in the deposits of Giorgio Franchetti Gallery at the Ca’ d’Oro (ML 202 and ML 233). The fragments are decorated with branches inhabited by two fantastic animals that can be identified with a Sphinx and a Manticore. In their literary history these creatures are often associated with Good (Sphinx) and Evil (Manticore). The presence of these animals confirms that the Ca’ d’Oro friezes belong to the Ravenna-Venetian culture, characterized by references to a late classical imagery enriched by Iranian-Sassanid iconography, widespread throughout the figurative production of the Mediterranean and in particular in Venice. The meaning of these animals is connected with encyclopaedic treatises of the Middle Ages, in particular with Bestiaries, illustrating the eternal conflict between Good and Evil, displayed at first in ecclesiastical buildings and subsequently also in private houses with apotropaic function, as we can see in many Venetian palaces.